Pilot project to study the association of troponin I with cardiovascular events in the population of Russian region - S. A. Shalnova; O. M. Drapkina; A. V. Kontsevaya; E. B. Yarovaya; V. A. Kutsenko; V. A. Metelskaya; A. V. Kapustina; Yu. A. Balanova; O. A. Litinskaya; M. S. Pokrovskaya (Кардиоваскулярная терапия и профилактика, 2021)
Aim. As part of a pilot study, to investigate the potential significance of cardiac troponin I (cTnI) in assessing the risk of cardiovascular diseases (CVD) in general population aged 35-64 years of one of the regions from the ESSE-RF study.Material and methods. The study is based on the ESSE-RF observational prospective study using a sample from one Russian region. The analysis included socio-demographic variables, risk factors, history of CVD. The cTnI level was measured from November to December 2021 in serum samples stored at -70° C using high sensitivity chemiluminescent microparticle immunoassay using Architect Stat High Sensitivity Troponin I (Abbott) reagents on an Architect i2000SR immunoassay analyzer (Abbott, Abbot Park IL USA). The endpoints were hard (cardiovascular death and myocardial infarction) and composite endpoints (cardiovascular death, new cases of myocardial infarction, stroke, coronary artery disease and revascularization). The median follow-up was 5,5 years. In total, the analysis included 1120 people aged 35-64 years.Results. Analysis of the associations between Systematic Coronary Risk Evaluation (SCORE) and cTnI showed a significant difference in risk stratification for these two parameters. In women from cTnI-related high-risk category for cardiovascular events (CVE), there were no endpoints at all. In men of moderate and high risk, the proportion of endpoints increases with increasing cTnI-related risk. The survival curves corresponding to first 3 quintiles of cTnI risk distribution did not diverge, and, therefore, the number of CVEs in these groups did not differ. At the same time, the curves corresponding to 4th and 5th quintiles significantly differed from the first 3 quintiles, which indicates a higher CVE risk in subjects from these groups (p<0,001). Considering that there were only 3 endpoints in cTnI-related high-risk group, a survival analysis was performed for low-risk versus moderate-high risk. The curves obtained diverge significantly (p=0.006). Cox proportional hazards models were analyzed to assess the relationship between the cTnI level and endpoints. It was shown that cTnI itself or its logarithm is significantly associated with hard and composite endpoints. The cTnI cut-off point of 12/10 pg/ml (males/females) was associated with hard endpoint, and 6/4 pg/ml — with composite one. It should be noted that the recommended cut-off point of 6/4 pg/ml is close to the upper quartile of cTnI distribution in the European population. For the Russian population, the upper quartile corresponds to cTnI level of 3,5/2,1 pg/ml, which indicates the need to reduce the critical cTnI values in Russia. To assess risk reclassification, Cox models were analyzed using the Net Reclassification Index (NRI), as well as NRIsurvival for survival analysis. For categorical variables, the NRIcategorial was used. Both methods of including cTnI in the model significantly improve the risk classification of severe endpoints in men.Conclusion. The results obtained confirm the need to lower the threshold values for predicting combined endpoints, in particular, in Russian men. cTnl has an independent effect on CVE risk and its addition to SCORE improves the prediction of CVEs among men. However, the data obtained are preliminary and require clarification sing larger sample. At the same time, it is obvious that the determination of cТnI level can play a significant role in cardiovascular risk assessment and be an unfavorable prognosis marker among Russian population.